STRUCTURAL AND SEMICONDUCTING PROPERTIES OF ZnTe THIN FILMS GALVANOSTATICALLY GROWN ONTO MONOCRYSTALLINE InP SUBSTRATE FROM TeCL4 /DMSO SOLUTION - GREZ,P (Sociedad Chilena de Química, 2007)
ZnTe thin films were galvanostatically electrodeposited onto (100) InP substrates from an electrolytic solution containing TeCl4 dissolved in DMSO. Cyclic voltammetry in the dark was used to identify the process involved in the complex electrochemical reduction of the Te(IV) precursor. Quantitative analysis of energy dispersive x-ray analysis results indicated that the composition ratio (Zn:Te) was not possible to determine due the presence of a tellurium excess in the deposits. X-ray diffraction results revealed that the thin films obtained showed a preferred (200) orientation with cubic structure indicating the existence of an epitaxial grow along the (100) crysytalline planes of the InP substrate. The n-type character of the films was deduced from Mott-Schottky plots that also gave a donor density of 1.54 x 10+18 cnr-3. From the optical absortion measurements a bandgap of 2.21 eV was obtained